RADIATION DERMATITIS—CLINICAL MANIFESTATIONS AND TREATMENT. AN ANALYSIS OF CURRENT RESEARCH - Magdalena Pietrzak; Mikołaj Wiśniewski; Karolina Barzyk; Agata Brzyska; Weronika Buczek; Jolanta Wiśniewska; Piotr Bartnik; Urszula Marzec (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Radiation-induced skin injury is a frequent adverse effect of radiotherapy, ranging from early erythema and desquamation to chronic fibrosis, pigment alteration, and telangiectasia. These reactions can reduce patient comfort, impair daily activities, and occasionally limit delivery of optimal cancer therapy. This review outlines current knowledge on mechanisms, prevention, and management of radiation-induced skin injury, including pharmacological, physical, and supportive strategies.Methodology: A targeted literature search was performed in a medical research database using terms related to radiation, radiotherapy, and management of skin reactions. Recent clinical trials, observational studies, and systematic reviews meeting inclusion criteria were analyzed to identify prevailing preventive and therapeutic approaches.Results: Skin injury results from DNA damage, inflammatory signaling, and oxidative stress affecting normal skin cells. Acute reactions typically occur within three months of exposure, whereas chronic changes may persist for years. Key risk factors include high radiation dose, sensitive anatomical sites such as thin or folded skin, and concurrent systemic cancer therapies. Evidence supports preventive measures including gentle cleansing, routine moisturization, topical corticosteroids, protective barrier films, and optimized radiation planning. Adjunctive treatments such as hyperbaric oxygen therapy, silver-based dressings, botanical products, and vitamin-based agents show potential benefit, although current evidence is limited by small sample sizes and methodological variability.Conclusion: Radiation-induced skin injury remains a clinical problem. Multimodal management combining standardized skin care, targeted pharmacologic treatments, and supportive interventions may reduce severity and improve patient outcomes. Further studies are required to define evidence-based management guidelines.